The Influence of Service Quality and Hotel Facilities on Repurchase Intention at Novotel Jakarta Gajah Mada - Dimas Dwi Putra; Violintikha Harmawan; Mutiara Fauzia Hikmawati (Journal of Multidimensional Management, 2026)
This study examines the effects of service quality and hotel facilities on repurchase intention among guests of Novotel Jakarta Gajah Mada. A quantitative causal-associative design was applied to 100 guests who had previously stayed at the hotel. Data were collected through a five-point Likert-scale questionnaire and analyzed using descriptive statistics, classical-assumption tests, and multiple linear regression in SPSS. The regression model was significant (F = 128.389, p < 0.001) and explained 72.6% of the variance in repurchase intention (R² = 0.726). Service quality had a positive and significant effect (B = 0.511, β = 0.608, t = 6.235, p < 0.001), as did hotel facilities (B = 0.250, β = 0.275, t = 2.816, p = 0.006). The larger standardized coefficient for service quality indicates that it was the more dominant predictor. The findings suggest that management should prioritize consistent, responsive, and friendly service while maintaining reliable Wi-Fi, water pressure, and parking arrangements to strengthen guests’ intention to return.